Ovulation rate in lines of rabbits selected on different criteria - Cifre J.; Vicente J.S.; Baselga M.; García-Ximénez F. (Rabbit production in hot climates, 1994)
Ovulation rate of several contemporaneous generations of three lines of rabbits selected for litter size at weaning or postweaning daily gain are analyzed. Some differences are observed between lines being the line selected for daily gain superior to one of the lines selected for litter size. Three different groups of hiperprolific (HH) females are compared in ovulation rate. There are not significant differences between criteria for sorting females as hiperprolific.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)